Eye Movements Reveal Fast, Voice-Specific Priming - Papesh, Megan H. (J Exp Psychol Gen, 2016)
In spoken word perception, voice specificity effects are well-documented: When people hear repeated words in some task, performance is generally better when repeated items are presented in their originally heard voices, relative to changed voices. A key theoretical question about voice specificity effects concerns their time-course: Some studies suggest that episodic traces exert their influence late in lexical processing (the time-course hypothesis; McLennan & Luce, 2005), whereas others suggest that episodic traces influence immediate, online processing. We report two eye-tracking studies investigating the time-course of voice-specific priming within and across cognitive tasks. In Experiment 1, participants performed modified lexical decision or semantic classification to words spoken by four speakers. The tasks required participants to click a red “×” or a blue “+” located randomly within separate visual half-fields, necessitating trial-by-trial visual search with consistent half-field response mapping. After a break, participants completed a second block with new and repeated items, half spoken in changed voices. Voice effects were robust very early, appearing in saccade initiation times. Experiment 2 replicated this pattern while changing tasks across blocks, ruling out a response priming account. In the General Discussion, we address the time-course hypothesis, focusing on the challenge it presents for empirical disconfirmation, and highlighting the broad importance of indexical effects, beyond studies of priming.